Protective anti‐prion antibodies in human immunoglobulin repertoires. Issue 9 (10th August 2020) - Senatore, Assunta; Frontzek, Karl; Emmenegger, Marc; Chincisan, Andra; Losa, Marco; Reimann, Regina; Horny, Geraldine; Guo, Jingjing; Fels, Sylvie; Sorce, Silvia; Zhu, Caihong; George, Nathalie; et al.
Abstract: Prion immunotherapy may hold great potential, but antibodies against certain PrP epitopes can be neurotoxic. Here, we identified > 6, 000 PrP‐binding antibodies in a synthetic human Fab phage display library, 49 of which we characterized in detail. Antibodies directed against the flexible tail of PrP conferred neuroprotection against infectious prions. We then mined published repertoires of circulating B cells from healthy humans and found antibodies similar to the protective phage‐derived antibodies. When expressed recombinantly, these antibodies exhibited anti‐PrP reactivity. Furthermore, we surveyed 48, 718 samples from 37, 894 hospital patients for the presence of anti‐PrP IgGs and found 21 high‐titer individuals. The clinical files of these individuals did not reveal any enrichment of specific pathologies, suggesting that anti‐PrP autoimmunity is innocuous. The existence of anti‐prion antibodies in unbiased human immunological repertoires suggests that they might clear nascent prions early in life. Combined with the reported lack of such antibodies in carriers of disease‐associated PRNP mutations, this suggests a link to the low incidence of spontaneous prion diseases in human populations. Synopsis: This study assessed the anti‐prion protein (PrP) immunoreactivity in human immunoglobulin repertoires and patient samples. Anti‐PrP autoimmunity can exist in human communities, appears to be innocuous, and may protect against prion infections. >6, 000 antibodies against various PrP epitopes were recovered from a synthetic human antibody (Fab) phage library. Of the phage display derived Fabs, 49 Fabs were characterized in detail. Fabs directed against the N‐terminal flexible tail of PrP conferred neuroprotection against infectious prions. HCDR3 sequences similar to a protective phage‐derived Fab were identified in published repertoires of B cells from healthy humans. When expressed recombinantly, these antibodies reacted to human PrP. By interrogating a large cohort of 37, 894 hospital patients, twenty‐one individuals with high‐titer anti‐PrP autoreactivity in the plasma were found. The presence of anti‐PrP autoantibodies did not correlate to any neurological condition or any other diseases. Abstract : This study assessed the anti‐prion protein (PrP) immunoreactivity in human immunoglobulin repertoires and patient samples. Anti‐PrP autoimmunity can exist in human communities, appears to be innocuous, and may protect against prion infections.